Cooperation With School Principals and Teachers Towards Developing Students' Malacts - Ani Apiyani (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Developing student morals is a crucial aspect of education which aims to shape student character and morals. This article discusses the importance of collaboration between school principals and teachers in strengthening student moral development. The school principal has a strategic role in setting the vision and mission, creating policies that support moral development, and building a positive school culture. Meanwhile, teachers act as role models, integrating moral values ​​in learning, and providing guidance and counseling to students. Effective collaboration between school principals and teachers can be carried out through regular coordination meetings, joint program development, and professional training. The result of this collaboration is improving student character, creating a harmonious school environment, and better academic achievement. In conclusion, synergy between school principals and teachers is the key to developing optimal student morals, producing a generation of achievers and noble characters.